A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae) - Yasunaga, Tomohide; Duwal, Ram Keshari; Oh, Minsuk; Lee, Seunghwan (Zootaxa, 2016)
The Indochinese phyline plant bugs, belonging to the recently established tribe Decomiini Schuh & Menard, are reviewed. Fourteen species in four genera, Decomia Poppius, Decomioides Schuh, Malaysiamiris Schuh and Rubrocuneocoris Schuh, are now recognized from Indochina, including a remarkable new species, Decomia ishikawai Yasunaga, Duwal & Lee n. sp., herein diagnosed, described and discussed. The male of Decomia nigrissima Yasunaga, described only on the holotype female, is for the first time reported. An annotated checklist and a key to genera and species are provided to facilitate identification of the Indochinese taxa of the Decomiini.